PENYULUHAN MANAJEMEN LUKA AKUT - Mhd Nurhuda; Yusti Siana; Yuliza Birman; Dian Puspita (Yayasan Nusantara Hasana Berdikari, 2023)
Wounds are discontinuities of epithelial tissue caused by traum taham, bluntness, temperature changes, exposure to currants, and animal bites, without any damage to tissues such as nerve tissue, muscle and bone. If the wound is not cleaned, there will be an invasion of harmful microorganisms that cause infection, especially in open wounds, so wound care is needed by improving hygiene. Acute injuries can be planned or unplanned, such as surgical wounds that are planned wounds performed in sterile rooms and using contamination-free tools. However, acute wounds are easily infected if wound care is not optimal so that it triggers inflammatory reactions. Solution The problem offered to the problems that occur to PKM partners is that the community does not understand about acute wound care so that the solution offered is in the form of counseling for acute wound care and management. The activity was carried out at the Ulak karang health center with 40 participants. The community was very enthusiastic about the counseling and socialization carried out by the team of doctors so that it went smoothly and was closed by a question and answer session and discussion.